Development of Heron’s cooperative inquiry model to improve narrative writing skills - Elisabet Janul; Dadang Sunendar (Inovasi Kurikulum, 2025)
This study aims to develop and implement a cooperative inquiry-based learning model to enhance elementary school students' narrative writing skills and creativity. The model is based on the Cooperative Inquiry theory, emphasizing collaboration, reflection, communication, and shared experiences among learners. This approach encourages active student engagement, enabling them to create knowledge and reflect on their learning experiences collaboratively. The study employed a mixed-methods approach, integrating quantitative and qualitative data. The research subjects were fifth-grade students from an elementary school in Bandung, Indonesia. Data were collected through pre-tests, post-tests, interviews, questionnaires, and observations to understand the model's impact comprehensively. The results revealed that the EIDCP (Experience, Interpreting, Discuss/Dialog, Co-create, Publish/Presentation) learning model significantly improved students' narrative writing skills and creativity. Furthermore, this model effectively strengthened students' collaboration skills, enhanced learning motivation, and fostered a more dynamic and participatory learning environment. Based on these findings, the cooperative inquiry-based learning model is recommended for broader implementation at the elementary school level as an effective strategy to enhance students’ literacy and creativity while supporting the development of their social skills.   Abstrak Penelitian ini bertujuan untuk mengembangkan dan menerapkan model pembelajaran kooperatif berbasis inkuiri guna meningkatkan keterampilan menulis narasi dan kreativitas peserta didik sekolah dasar. Model ini didasarkan pada teori Inkuiri Kooperatif yang menekankan kolaborasi, refleksi, komunikasi, dan pengalaman bersama di antara peserta didik. Pendekatan ini dirancang untuk mendorong keterlibatan aktif peserta didik, memungkinkan mereka secara bersama-sama menciptakan pengetahuan serta merefleksikan pengalaman belajar mereka. Penelitian ini menggunakan metode campuran dengan pendekatan kuantitatif dan kualitatif. Subjek penelitian adalah peserta didik kelas V di sebuah sekolah dasar di Bandung, Indonesia. Data dikumpulkan melalui pre-test, post-test, wawancara, kuesioner, dan observasi untuk memperoleh pemahaman menyeluruh mengenai dampak penerapan model ini. Hasil penelitian menunjukkan bahwa model pembelajaran berbasis siklus EIDCP (Experience, Interpreting, Discuss/Dialog, Co-create, Publish/Presentation) secara signifikan meningkatkan keterampilan menulis narasi dan kreativitas peserta didik. Selain itu, model ini juga terbukti efektif dalam memperkuat keterampilan kolaborasi peserta didik, meningkatkan motivasi belajar, dan menciptakan suasana pembelajaran yang lebih dinamis dan partisipatif. Berdasarkan temuan ini, model pembelajaran kooperatif berbasis inkuiri disarankan untuk diterapkan secara luas di tingkat sekolah dasar sebagai strategi yang efektif untuk meningkatkan literasi dan kreativitas peserta didik, sekaligus mendukung pengembangan keterampilan sosial mereka. Kata Kunci: menulis narasi; pembelajaran berbasis inkuiri; pembelajaran kooperatif